2020
DOI: 10.1111/pbi.13318
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and signalling pathways of dry fruit size: targets for genome editing‐based crop improvement

Abstract: Summary Fruit is seed‐bearing structures specific to angiosperm that form from the gynoecium after flowering. Fruit size is an important fitness character for plant evolution and an agronomical trait for crop domestication/improvement. Despite the functional and economic importance of fruit size, the underlying genes and mechanisms are poorly understood, especially for dry fruit types. Improving our understanding of the genomic basis for fruit size opens the potential to apply gene‐editing technology such as C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 152 publications
(195 reference statements)
2
41
0
Order By: Relevance
“…Increases in auxin similarly stimulate cell division in GA‐deficient tomato ( gib‐3 mutant lines) during early growth while applications of GA to auxin‐insensitive plants ( dgt mutant lines) have a minimal effect on cell division, which supports the notion that auxin is mainly necessary for the early cell proliferation phase (Liu et al ., 2016). With respect to GA, GA3ox is expressed during silique development in Arabidopsis in the replum, funiculus, and receptacle (Hussain et al ., 2020), and three distinct GA receptor genes ( CaGID1b . 1 , CaGID1b .…”
Section: Fruit Growth (Cell Division and Expansion)mentioning
confidence: 99%
See 2 more Smart Citations
“…Increases in auxin similarly stimulate cell division in GA‐deficient tomato ( gib‐3 mutant lines) during early growth while applications of GA to auxin‐insensitive plants ( dgt mutant lines) have a minimal effect on cell division, which supports the notion that auxin is mainly necessary for the early cell proliferation phase (Liu et al ., 2016). With respect to GA, GA3ox is expressed during silique development in Arabidopsis in the replum, funiculus, and receptacle (Hussain et al ., 2020), and three distinct GA receptor genes ( CaGID1b . 1 , CaGID1b .…”
Section: Fruit Growth (Cell Division and Expansion)mentioning
confidence: 99%
“…During fruit development, CKs bind to histidine kinases (HKs), which donate phosphate groups to downstream response elements via the action of AHPs. Consequently, a mutation reducing AHP activity results in CK insensitivity and smaller siliques, while attenuated CKX expression leads to increased CK and larger siliques (Hussain et al ., 2020). In Arabidopsis, as well as in strawberry, BRs function alongside other phytohormones in controlling fruit size.…”
Section: Fruit Growth (Cell Division and Expansion)mentioning
confidence: 99%
See 1 more Smart Citation
“…Glutathione metabolism removes free radicals and prevents oxidative damage to DNA, proteins and lipids. Ascorbic acid (antioxidant) functions as a cofactor for enzymes in photosynthesis, and the synthesis of plant hormones [19] and affects gene expression and transcription, cell division, and growth [20].…”
Section: Validation Of Differential Expressed Genes By Rt-qpcrmentioning
confidence: 99%
“…These genes include SP (SELF-PRUNING) [47], fw2.2 (FRUIT WEIGHT 2.2) [48], FASCIATED [49], and MULTIFLORA [50]. Previous studies had demonstrated that the genetic regulation networks of agronomic traits were conserved in different plant taxa, which suggested that editing the homolog genes across species may generate similar phenotypes [51]. We suggested that the domestication knowledge from model crops could be translated into tobacco for the generation of high seed yield and high lipid content varieties.…”
Section: Crispr-cas9 System Could Be Used For De Novo Tobacco Domestimentioning
confidence: 99%